INHIBITORY EFFECT OF ANTIFUNGAL ACTIVITY OF GROUND NUT OIL AGENT’S FUNGI (International Association of Biologicals and Computational Digest, 2022)
Ground nut (Arachis hypogaea) oil is essential component of our food and it can inhibit the spore germination of Aspergillus sp. The development of protective components with natural origin as alternatives to synthetic fungicides is currently in the spotlight. This oil is known for their broad spectrum of antifungal activity against plant pathogen and human both. The essential oils reduce hyphal growth and induce cell lysis and cytoplasmic evacuation in fungi.
Keywords: Aspergillus, Fungus, Ground nut, Oil.